Clinical, Electrocardiographic and Echocardiographic Profile of Ischemic Cardiomyopathy: An analysis of 100 cases. - Islam, Mainul; Ali, M Atahar; Ferdaushi, Umme Habiba; Nabi, Shaila; Khan, Sayeedur Rahman; Islam, Md Shariful; Mahmoud, Hasan (Bangladesh Heart Journal, 2021)
Background: Ischemic heart disease (IHD) is one of the leading cause of morbidity and mortality worldwide. Ischemic cardiomyopathy (ICM) is a delayed complication of IHD that arises as dilated cardiomyopathy with depressed ventricular function, which cannot be attributed entirely to coronary artery obstruction or ischemic injury. Objectives: To evaluate the clinical, electrocardiographic and echocardiographic profile of patients presenting with ischemic cardiomyopathy. Methods: In this cross sectional observational study 100 patients of ischemic cardiomyopathy admitted in hospital or visited OPD in NICVD, Dhaka from March’15 to Sept’15 were studied. Enrollment of the patients were done after fulfilling the inclusion and exclusion criteria. Clinical, electrocardiographic and echocardiographic data were collected then data analysis was done. Results: Data analysis of 100 patients was showed age range was 40-80 years and mean age was 61.4±7.9 years. 79% subjects were male. Most common symptoms were dyspnea (93%), chest pain(73%), palpitation (39%) and edema (23%). Most patients were in NYHA functional class lV (43%). 64% cases had history of anterior myocardial infarction (MI), 22% had inferior MI, 25% had H/O PTCA and 7% had CABG. 71% subjects had tachycardia, 65% had lungs basal rales, 56% had systolic blood pressure below 100 mmhg and 25% had edema. ECG findings was as follows sinus rhythm (85%), Sinus tachycardia 71%, AF 15%, LBBB 34%, RBBB 12%, pathological Q in anterior surface 65% and inferior surface 21%, non specific ST-T changes 41% and PVCs was found in 17%.On echocardiography ,anterior wall hypokinesia was seen in 52% and global hypokinesia in 43%. Mean left ventricular ejection fraction (LVEF) was 31±5.9% and mean left ventricular internal diastolic diameter (LVIDd) was 6.5±0.4 cm. (59%) subjects had mitral regurgitation (MR) grade-l and 20% had MR grade-ll. Conclusion: The clinical presentation of ischemic cardiomyopathy varies from patient to patient. Severity of symptoms correlates with severity of left ventricular systolic dysfunction, left ventricular diameter and mitral regurgitation grade . Anterior Myocardial infarction has more chance to develop ischemic cardiomyopathy. Bangladesh Heart Journal 2020; 35(2) : 121-127